Chemical looping reforming of ethanol for syngas generation: A theoretical investigation. (2nd February 2012) - Kale, Ganesh R.; Kulkarni, Bhaskar D.; Bharadwaj, K. V.
SUMMARY Chemical looping reforming (CLR) is a novel technology that can be used for reforming of cheaply available abundant biofuel like ethanol for the production of hydrogen/syngas for fuel cells. A systematic thermodynamic study for the CLR process using selected oxygen carriers was done to analyze the products and energy requirements of the CLR process in the temperature range of 500–1200 °C at 1 bar pressure for ethanol. The results showed favorable conditions for syngas manufacture from this process. Fe2O3 was found to be the best performing oxygen carrier followed by calcium and sodium sulfates, while Mn oxides were the least preferred oxygen carriers for CLR of ethanol process. The optimum process temperature was found to be 1000 °C. The actual CLR‐ethanol process shows exothermicity against the theoretical endothermic partial oxidation of ethanol. The results obtained in this theoretical study can pave the way for experimental programs for syngas generation for SOFC‐type fuel cells. Similar studies can be undertaken for other fuels for fuel processor development by CLR process. Copyright © 2012 John Wiley & Sons, Ltd.